2006
DOI: 10.1016/j.bbamcr.2006.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic functions of glycosomes in trypanosomatids

Abstract: Protozoan Kinetoplastida, including the pathogenic trypanosomatids of the genera Trypanosoma and Leishmania, compartmentalize several important metabolic systems in their peroxisomes which are designated glycosomes. The enzymatic content of these organelles may vary considerably during the life-cycle of most trypanosomatid parasites which often are transmitted between their mammalian hosts by insects. The glycosomes of the Trypanosoma brucei form living in the mammalian bloodstream display the highest level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
269
1
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(285 citation statements)
references
References 104 publications
4
269
1
11
Order By: Relevance
“…These include the glycosomes, peroxisome-related microbodies that contain enzymes of several important metabolic pathways including glycolysis, the pentose-phosphate pathway, b-oxidation of fatty acids, gluconeogenesis, purine salvage, and biosynthesis of pyrimidines, ether lipids and squalenes. 23 Compartmentalization of metabolic pathways in this manner prevents the accumulation of toxic intermediates which would otherwise damage the cell, 24 and is also thought to facilitate rapid metabolic adaptation in response to changing environments. 23 Studies in both Leishmania and trypanosomes have shown that proper biogenesis of glycosomes and the correct targeting of glycosomal enzymes are essential for parasite survival, [24][25][26][27][28][29] making these unique organelles an attractive drug target.…”
Section: Introductionmentioning
confidence: 99%
“…These include the glycosomes, peroxisome-related microbodies that contain enzymes of several important metabolic pathways including glycolysis, the pentose-phosphate pathway, b-oxidation of fatty acids, gluconeogenesis, purine salvage, and biosynthesis of pyrimidines, ether lipids and squalenes. 23 Compartmentalization of metabolic pathways in this manner prevents the accumulation of toxic intermediates which would otherwise damage the cell, 24 and is also thought to facilitate rapid metabolic adaptation in response to changing environments. 23 Studies in both Leishmania and trypanosomes have shown that proper biogenesis of glycosomes and the correct targeting of glycosomal enzymes are essential for parasite survival, [24][25][26][27][28][29] making these unique organelles an attractive drug target.…”
Section: Introductionmentioning
confidence: 99%
“…The subcellular compartmentalization of glycolysis in trypanosomatids is fundamentally different than in all other eukaryotes, where glycolysis ensues cytoplasmically. In trypanosomatids, the majority of glycolytic enzymes are contained in unusual peroxisome-like organelles termed 'glycosomes'; only the terminal three glycolytic enzymes are cytosolic 48,49 (see Figure 3). Thus in trypanosomatids, GAPDH and enolase exist in distinct intracellular locales and are unassociated.…”
Section: Apoptotic Mimicrymentioning
confidence: 99%
“…This 'reversed' behavior was attributable genetically to E1B 19 K. That authentic Bcl-2 could substitute for E1B 19 K, but that it does not program such a reversed behavior in the context of Figure 3 Glycosomal localization of glycolytic enzymes. Enzymes and intermediates of glycolysis that are found within and without the glycosome 48,49 are diagrammed here. Glycosomes are intracellular peroxisome-like organelles of trypanosomatids, constrained by a single lipid bilayer membrane (represented by a double solid line), within which the proximal steps of glycolysis ensue.…”
Section: Reprogrammed Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, enzimas relacionadas a outras vias, como β-oxidação de ácidos graxos, recrutamento de purinas e vias biossintéticas para pirimidinas podem estar presentes nos glicossomos (Michels et al, 2006). Outras organelas encontradas no citoplasma de T. cruzi são os reservossomos e os acidocalcisomas.…”
Section: Ultraestruturaunclassified